Experimental and simulation analysis of energy absorption capacity of 3D printed structure design (F) - Danish Aniki Anwari (Nanyang Technological University, 2024)
This research investigates the energy absorption capacity of an open-cell foam 3D structure through simulation of compression tests. The study utilises AutoCAD software, particularly Rhino 3D, for modelling the foam structures, generating multiple models of varying volumes. Subsequently, Ansys Workbench simulation software is employed to simulate the compression process, yielding insights into deformation, stress distribution, and force reactions. One significant challenge encountered during the research pertained to generating a random Voronoi tessellation of the structures, which led to improper meshing during simulation. Despite this obstacle, the study provides valuable insights into the energy absorption capabilities of open-cell foam structures, offering implications for various engineering applications where energy dissipation is crucial.